Etching agent for observing chromium carbide in stainless steel and preparation method and application thereof

By optimizing the ratio of hydrochloric acid to water and adding ethanol, a erosive agent dedicated to observing chromium carbides in stainless steel was prepared, which solved the problem of difficulty in observing chromium carbides in the prior art, and achieved a clear display of chromium carbide boundaries and Improve the accuracy of analysis.

CN119491227APending Publication Date: 2025-02-21INDONESIA GUANGQING NICKEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385749.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing corrosion agents have problems of strong corrosiveness, non-uniform corrosion and chromium carbide shedding when showing chromium carbides in 304 austenitic stainless steel, making it difficult to accurately observe their morphology and distribution.

Method used

By optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol, an erosive agent specially used to observe chromium carbides in stainless steel was prepared, including 15-20 parts of water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol, 3-5 parts of ferric chloride.

Benefits of technology

This erosive agent can clearly display the boundaries of chromium carbides in 304 austenitic stainless steel, ensuring that chromium carbide particles are not easy to fall off, and facilitate the observation of their microstructure and the accuracy of the analysis of related component content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491227A_ABST
    Figure CN119491227A_ABST
Patent Text Reader

Abstract

The invention discloses an aggressive agent for observing chromium carbides in stainless steel as well as a preparation method and application of the aggressive agent. The aggressive agent comprises the following components in parts by weight: 15-20 parts of water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol and 3-5 parts of ferric trichloride. The erosion agent special for observing the chromium carbide is prepared by optimizing the ratio of hydrochloric acid to water and adding a proper amount of ethyl alcohol, and the eroded chromium carbide is in a bright white ball shape, a water drop shape or a granular shape with a clear boundary and is embedded at a crystal boundary or in a crystal grain; the form of the precipitated chromium carbide in the stainless steel can be clearly observed, and the component content of the stainless steel can be analyzed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material etchants, and more particularly to an etchant for observing chromium carbides in stainless steel, a preparation method and an application thereof. Background Art

[0002] 304 austenitic stainless steel is a widely used austenitic stainless steel, known for its excellent corrosion resistance, mechanical strength and good machinability. Its main chemical composition includes about 18% chromium and 8% nickel, in addition to small amounts of carbon, manganese, silicon and other elements. 304 stainless steel is widely used in equipment and structure manufacturing in industries such as petrochemicals, construction, and food processing due to its durability in a variety of environments. In common 304 austenitic stainless steel, carbon is completely dissolved in the austenite matrix at high temperatures. When cooled to room temperature, carbon exists in the matrix in a supersaturated state. When the material is heated to the appropriate temperature again and maintained for a certain period of time, the carbon atoms will react with the chromium atoms to form chromium carbides (CrxC y ). The precipitation of chromium carbides has a significant effect on the corrosion resistance of 304 austenitic stainless steel. As chromium carbides precipitate at the grain boundaries, the chromium content near the grain boundaries is significantly reduced, resulting in chromium depletion in local areas. Chromium-depleted areas are prone to intergranular corrosion in corrosive media, a phenomenon that not only weakens the overall corrosion resistance of the material, but may even lead to structural failure.

[0003] At present, the chemical etchants commonly used in the metallographic inspection of 304 austenitic stainless steel mainly include aqua regia (3 parts hydrochloric acid + 1 part nitric acid) and ferric chloride hydrochloric acid aqueous solution (5 grams of ferric chloride + 50 milliliters of hydrochloric acid + 100 milliliters of water). Before use, the etchant needs to be prepared in a certain proportion. The aqua regia needs to be left to stand for 24 hours before use, while the ferric chloride hydrochloric acid aqueous solution can be used as soon as it is prepared. In actual operation, the polished sample surface is gently rubbed with a cotton ball dipped in the etchant for a few seconds until the sample surface appears dark gray, and then the sample surface is rinsed with water to remove the etchant residue, followed by cleaning with anhydrous ethanol, and then dried with a hair dryer for microstructural observation. However, these two etchants have the following defects when displaying chromium carbides:

[0004] The strong corrosiveness and high volatility of aqua regia, as well as the non-uniformity of corrosion of ferric chloride hydrochloric acid aqueous solution, can easily cause chromium carbides to fall off during the corrosion process, or cause local black holes to appear on the eroded surface, thus affecting the subsequent accurate analysis of the morphology and distribution of chromium carbides. The morphology and distribution characteristics of chromium carbides are important factors that affect and regulate the performance of 304 austenitic stainless steel. Current etchants cannot effectively observe the morphology and distribution characteristics of chromium carbides in 304 austenitic stainless steel.

[0005] Therefore, an improved method that can simply and effectively display the precipitation morphology and distribution of chromium carbides in 304 austenitic stainless steel is urgently needed to support related research and applications. Summary of the invention

[0006] In view of the above technical problems, the present invention provides an etchant for observing chromium carbides in stainless steel, and a preparation method and application thereof.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions:

[0008] An etchant for observing chromium carbides in stainless steel, characterized by comprising the following components in parts by weight: 15-20 parts of water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol, and 3-5 parts of ferric chloride.

[0009] This application is based on the formula of ferric chloride hydrochloric acid aqueous solution, which is commonly used as an etchant for traditional austenitic stainless steel. By optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol, an etchant specifically for observing chromium carbides is prepared. By reasonably matching ethanol, water and ferric chloride, the components in the etchant can coordinate and support each other, and the erosion ability of the etchant is controlled within a moderate range, achieving the invention purpose of being able to clearly observe the chromium carbides of 304 austenitic stainless steel after corrosion.

[0010] Furthermore, the hydrochloric acid is analytically pure hydrochloric acid, and the ethanol is anhydrous ethanol. Analytically pure hydrochloric acid has higher purity and fewer impurities than ordinary hydrochloric acid, and is suitable for precise analysis and determination. Analytically pure reagents have higher purity than ordinary reagents, a high content of main components, and very low interfering impurities, and are more suitable for research on precise analysis and determination.

[0011] An application of the above-mentioned etchant for observing chromium carbides in stainless steel is in 304 austenitic stainless steel.

[0012] 304 austenitic stainless steel is a very common stainless steel with excellent corrosion resistance. When corroding stainless steel, it is necessary to select the corresponding corrosive agent according to the specific purpose of corrosion. For example, the two corrosive agents for observing austenite structure and observing chromium carbide cannot be mixed.

[0013] Further, the etchant is used to etch 304 austenitic stainless steel, and chromium carbides in the 304 austenitic stainless steel can be observed after etching. The 304 austenitic stainless steel is silvery white in color, and when the etchant is used to etch it until it turns dark gray, it is convenient to clearly observe the morphology and distribution of chromium carbides later.

[0014] Furthermore, the 304 austenitic stainless steel erosion surface is immersed in the erosion agent for erosion for 3-5 seconds, and the erosion is terminated when the 304 austenitic stainless steel erosion surface turns dark gray.

[0015] Reasonable etching time is very important for observing the morphology of chromium carbides in 304 austenitic stainless steel. An etching time of 3-5s can ensure that the eroded surface is dark gray after etching, thus achieving good observation effect.

[0016] Furthermore, the method for stopping corrosion specifically includes: taking out the 304 austenitic stainless steel and washing it with deionized water, and then cleaning the eroded surface with anhydrous ethanol.

[0017] Deionized water can wash away organic matter and inorganic salts on the surface of 304 austenitic stainless steel. Anhydrous ethanol, as a non-polar solvent, has a good degreasing effect on stainless steel with oily surface pollution and can quickly dissolve the oil on the surface. Using water and anhydrous ethanol to clean the eroded surface in turn can quickly stop the erosion and prevent the corrosive agent from continuing to erode the chromium carbides precipitated in the stainless steel.

[0018] Furthermore, before the 304 austenitic stainless steel erosion surface is immersed in the etchant for erosion, the process also includes: grinding and polishing the 304 austenitic stainless steel erosion surface. The purpose of grinding and polishing before erosion is mainly to eliminate the uneven structure and organization of the 304 austenitic stainless steel erosion surface, and to remove the dirt on its surface, so that the erosion surface has the required smoothness and cleanliness, and is convenient for the etchant to erode, thereby obtaining more accurate and reliable observation results. If there are scratches, oxides, dirt and other undesirable substances on the erosion surface, it will greatly affect the reaction rate and degree of the erosion, which is not conducive to observing the morphology of chromium carbides precipitated in the 304 austenitic stainless steel.

[0019] The specific grinding and polishing operation includes: grinding the 304 austenitic stainless steel sample on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polishing it on a polishing machine with 2.5μm diamond grinding paste until the surface of the 304 austenitic stainless steel sample is as smooth as a mirror without obvious scratches. After polishing, rinse the polished surface with ethanol and then dry it for erosion.

[0020] Furthermore, after the grinding and polishing, the 304 austenitic stainless steel erosion surface is cleaned with ethanol. Alcohol can effectively remove dirt and grease on the stainless steel surface, preventing the residual dirt and grease on the stainless steel surface from affecting subsequent erosion.

[0021] A method for preparing an etchant for observing chromium carbides in stainless steel comprises: uniformly mixing 15-20 parts by weight of water, 5.9-11.8 parts by weight of hydrochloric acid, 3.9-7.9 parts by weight of ethanol, and 3-5 parts by weight of ferric chloride to prepare an etchant. The present application prepares an etchant specifically for observing chromium carbides in stainless steel by optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol. After etching, the boundaries of chromium carbides can be clearly observed, which is convenient for subsequent accurate analysis of the morphology and distribution of chromium carbides.

[0022] Further, the specific method of mixing uniformly comprises: pouring hydrochloric acid and ethanol into water in turn and mixing, adding ferric chloride and mixing uniformly. Analytical pure hydrochloric acid is a strong acid with strong corrosiveness, while analytical pure anhydrous ethanol is a flammable liquid. By first pouring analytical pure hydrochloric acid into deionized water, the purpose of diluting analytical pure hydrochloric acid can be achieved, and its corrosiveness can be weakened. After adding analytical pure anhydrous ethanol, concentrated hydrochloric acid can be further diluted to reduce the overall concentration of the etchant. And because the polarity of the two is different, ethanol and water are used as solvents together, and have good mutual solubility with ferric chloride, which can increase the erosion rate and ensure the uniformity of the erosion process.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present application is based on the formula of ferric chloride hydrochloric acid aqueous solution, which is a commonly used etchant for traditional austenitic stainless steel. By optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol, an etchant specifically used for observing chromium carbides in stainless steel is prepared. The chromium carbides after etching are bright white spheres, droplets or granules with clear boundaries, embedded in the grain boundaries or inside the grains.

[0025] First of all, the hydrochloric acid in the component not only effectively guarantees the erosion ability of the etchant, but also can ionize H + and Cl- ions, thereby inhibiting Fe 3+ The hydrolysis reaction maintains Fe 3+ The effective concentration of Fe 3+ Oxidation of the substrate.

[0026] Secondly, ethanol and water as solvents can dilute hydrochloric acid and reduce the overall concentration of the etchant, thereby slowing down the erosion depth in local areas. In addition, since the hydroxyl group (-OH) in the ethanol molecule is the polar part, and the ethyl group (-C2H5) is the non-polar part, the polarity of the ethanol molecule is lower than that of the water molecule (the dipole moment of ethanol is about 1.69D, while the dipole moment of the water molecule is 1.85D). The coordination between the two can control the erosion ability of the reagent within a moderate range, avoid the chromium carbide from falling off during the erosion process, or cause local black holes to appear on the eroded surface, thereby affecting the subsequent accurate observation and analysis of the morphology and distribution of chromium carbides; if only anhydrous ethanol is used as a solvent, it is difficult to achieve this effect.

[0027] Finally, ethanol and water solvents have good miscibility with ferric chloride, which can increase the reaction rate and ensure the uniformity of the etching process.

[0028] The mutual coordination between the above components enables the improved etchant to control the erosion ability and erosion rate within a moderate range and ensure the uniformity of the erosion process, thereby clearly displaying the chromium carbide boundaries. The chromium carbide particles after etching are not easy to fall off, which is conducive to the observation of its microstructure and improves the accuracy of the analysis of the content of related components. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0031] In the attached figure:

[0032] Figure 1 The observation result of the eroded surface of 304 austenitic stainless steel in Example 3 under the electron microscope 2000X field of view after erosion;

[0033] Figure 2 The observation result of the eroded surface of 304 austenitic stainless steel in Example 3 under the electron microscope 10000X field of view after erosion;

[0034] Figure 3 The results are the observation results of the eroded surface of the comparative example 304 austenitic stainless steel under the electron microscope 5000X field of view after erosion. DETAILED DESCRIPTION

[0035] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Modifications or substitutions made to the methods, steps or conditions of the present invention without departing from the spirit and essence of the present invention are within the scope of protection of the present invention. Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the examples of the present invention are all commercially available; unless otherwise specified, all technical means in the examples of the present invention are conventional means well known to those skilled in the art.

[0036] The present application provides an etchant for observing chromium carbides in stainless steel, comprising the following components by weight: 15-20 parts of deionized water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol, and 3-5 parts of ferric chloride. Specifically, the etchant components are: 15-20 ml of deionized water, 5-10 ml of analytically pure hydrochloric acid, 5-10 ml of analytically pure anhydrous ethanol, and 3-5 grams of analytically pure ferric chloride. According to the density of deionized water being 1g / ml, the density of analytically pure hydrochloric acid being 1.18g / ml, and the density of anhydrous ethanol being 0.789g / ml, the above components by weight can be obtained. The present application provides an etchant for observing chromium carbides in stainless steel, and the etchant is used to erode 304 austenitic stainless steel, and chromium carbides in 304 austenitic stainless steel can be observed after erosion.

[0037] Specific methods for attacking 304 austenitic stainless steel include:

[0038] S1: 304 austenitic stainless steel pretreatment; specifically including:

[0039] The 304 austenitic stainless steel sample was ground on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polished on a polishing machine with 2.5μm diamond grinding paste until the surface of the 304 austenitic stainless steel sample was as smooth as a mirror without obvious scratches. After polishing, the polished surface was rinsed with ethanol and then dried to prepare for erosion.

[0040] S2: By weight, 15-20 parts of deionized water, 5.9-11.8 parts of analytically pure hydrochloric acid, 3.9-7.9 parts of analytically pure anhydrous ethanol, and 3-5 parts of analytically pure ferric chloride are mixed evenly to obtain an etchant; specifically comprising:

[0041] Analytical pure hydrochloric acid and analytical pure anhydrous ethanol are sequentially poured into deionized water and mixed, and then analytical pure ferric chloride solid is added and mixed evenly to obtain an etching agent.

[0042] S3: Immerse the 304 austenitic stainless steel erosion surface into the etchant for etching. When the 304 austenitic stainless steel erosion surface turns dark gray, the etching is terminated. Specifically include:

[0043] Immerse the 304 austenitic stainless steel erosion surface in the etchant. The erosion time is usually 3-5 seconds. The color change of the erosion surface can be observed. When the erosion surface turns into a slightly dark gray, take out the 304 austenitic stainless steel and immediately rinse it with deionized water. Then, quickly clean the erosion surface of the sample with anhydrous ethanol.

[0044] The present application provides a method for preparing an etchant for observing chromium carbides in stainless steel, comprising: uniformly mixing 15-20 parts by weight of water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol, and 3-5 parts of ferric chloride to prepare the etchant; a specific method for uniformly mixing comprises: pouring hydrochloric acid and ethanol into water in sequence and mixing, and adding ferric chloride and mixing uniformly.

[0045] This application is based on the formula of ferric chloride hydrochloric acid aqueous solution, which is commonly used as an etchant for traditional austenitic stainless steel. By optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol, an etchant specifically used for observing chromium carbides is prepared. The etchant formula in this application is ferric chloride hydrochloric acid alcohol aqueous solution, and the ferric chloride hydrochloric acid alcohol aqueous solution has the following differences from ferric chloride hydrochloric acid aqueous solution and ferric chloride hydrochloric acid alcohol solution:

[0046] First, let’s talk about the recipe:

[0047] The components of the ferric chloride hydrochloric acid aqueous solution include: ferric chloride + hydrochloric acid + water; the components of the ferric chloride hydrochloric acid alcohol solution include: ferric chloride + hydrochloric acid + anhydrous ethanol; the components of the ferric chloride hydrochloric acid alcohol aqueous solution include: ferric chloride + hydrochloric acid + anhydrous ethanol + water.

[0048] The above three solutions belong to different formulas. The ferric chloride hydrochloric acid aqueous solution and the ferric chloride hydrochloric acid alcohol solution have high acid concentration, strong solution polarity and strong corrosive ability, so that the chromium carbides in the austenitic stainless steel structure are completely corroded to form cavities or pits, making it impossible to accurately observe the morphology of chromium carbides.

[0049] At the same time, the purpose of this application is to observe chromium carbides in stainless steel. Unlike observing austenitic stainless steel structure, chromium carbides belong to the precipitated phase in stainless steel, while stainless steel structure refers to the organizational morphology of stainless steel itself, for example, the original organizational morphology of austenitic stainless steel refers to austenite structure + ferrite structure. Ferric chloride hydrochloric acid aqueous solution and ferric chloride hydrochloric acid alcohol solution can corrode stainless steel and observe the organizational morphology of austenitic stainless steel, but cannot show the morphology of chromium carbides.

[0050] The ferric chloride hydrochloric acid alcohol aqueous solution in the present application is formed by optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol to form a special etchant for observing chromium carbides in stainless steel. The hydrochloric acid in the components of the present application not only effectively guarantees the erosion ability of the etchant, but also the hydrochloric acid can ionize H +and Cl- ions, thereby inhibiting Fe 3+ The hydrolysis reaction maintains Fe 3+ The effective concentration of Fe 3+ Oxidation effect on the matrix. The ethanol and water used in the present application are used as solvents to dilute hydrochloric acid and reduce the overall concentration of the etchant, thereby slowing down the erosion depth in local areas. In addition, since the hydroxyl group (-OH) in the ethanol molecule is a polar part, and the ethyl group (-C2H5) is a non-polar part, this makes the polarity of the ethanol molecule lower than that of the water molecule (the dipole moment of ethanol is about 1.69D, while the dipole moment of the water molecule is 1.85D). The coordination between the two can control the erosion ability of the reagent within a moderate range, avoid the chromium carbide from falling off during the erosion process, or cause local black holes to appear on the erosion surface, thereby affecting the subsequent accurate observation and analysis of the morphology and distribution of chromium carbides; the ethanol and water acting solvents of the present application have good mutual solubility with ferric chloride, which can increase the reaction rate and ensure the uniformity of the erosion process. It is thereby ensured that the chromium carbides in the eroded surface of the stainless steel after erosion by the present application are bright white spheres, droplets or granules with clear boundaries, embedded in the grain boundaries or inside the grains.

[0051] The composition of 304 austenite used in the following examples and comparative examples conforms to the element range specified in ASTM-A240, wherein the steel grade composition requirements of S304 austenitic stainless steel in the ASTM-A240 standard are shown in Table 1.

[0052] Table 1 S30400 steel composition requirements in ASTM-A240 standard

[0053]

[0054] Example 1

[0055] The present embodiment provides an etchant comprising 15 ml of deionized water, 10 ml of analytical grade hydrochloric acid, 5 ml of analytical grade anhydrous ethanol, and 5 g of analytical grade ferric chloride.

[0056] The preparation method and application method of the above-mentioned etchant include:

[0057] S1: Pretreatment of 304 austenitic stainless steel. The 304 austenitic stainless steel samples were ground on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polished on a polishing machine with 2.5μm diamond paste until the sample surface was as smooth as a mirror without obvious scratches. After polishing, the surface was rinsed with ethanol and then blown dry with a polishing machine to prepare for erosion.

[0058] S2: Take 10 ml of analytical pure hydrochloric acid and 5 ml of analytical pure anhydrous ethanol, pour them into 15 ml of deionized water, mix them, then add 5 g of analytical pure ferric chloride solid and mix them evenly to obtain an etchant. Gently shake the volumetric flask containing the etchant to make the etchant solution uniform, and then pour the etchant into the beaker.

[0059] S3: Use tweezers to pick up the polished 304 austenitic stainless steel metallographic sample containing chromium carbide, immerse it into the etchant with the etched surface facing down for 4 seconds, observe the change in surface color, the surface of the sample is slightly dark gray, take out the sample and immediately rinse it with water, then quickly clean the etched surface of the sample with anhydrous ethanol, and then dry it with a hair dryer.

[0060] Example 2

[0061] The present embodiment provides an etchant comprising 20 ml of deionized water, 5 ml of analytical grade hydrochloric acid, 10 ml of analytical grade anhydrous ethanol, and 3 g of analytical grade ferric chloride.

[0062] The preparation method and application method of the above-mentioned etchant include:

[0063] S1: Pretreatment of 304 austenitic stainless steel. The 304 austenitic stainless steel samples were ground on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polished on a polishing machine with 2.5μm diamond paste until the sample surface was as smooth as a mirror without obvious scratches. After polishing, the surface was rinsed with ethanol and then blown dry with a polishing machine to prepare for erosion.

[0064] S2: Take 5 ml of analytical pure hydrochloric acid and 10 ml of analytical pure anhydrous ethanol, pour them into 20 ml of deionized water, mix them, then add 3 g of analytical pure ferric chloride solid and mix them evenly to obtain an etchant. Gently shake the volumetric flask containing the etchant to make the etchant solution uniform, and then pour the etchant into the beaker.

[0065] S3: Use tweezers to pick up the polished 304 austenitic stainless steel metallographic sample containing chromium carbide, immerse it into the etchant with the etched surface facing down for 4 seconds, observe the change in surface color, the surface of the sample is slightly dark gray, take out the sample and immediately rinse it with water, then quickly clean the etched surface of the sample with anhydrous ethanol, and then dry it with a hair dryer.

[0066] Example 3

[0067] The present embodiment provides an etchant comprising 17 ml of deionized water, 6 ml of analytical grade hydrochloric acid, 8 ml of analytical grade anhydrous ethanol, and 4 g of analytical grade ferric chloride.

[0068] The preparation method and application method of the above-mentioned etchant include:

[0069] S1: Pretreatment of 304 austenitic stainless steel. The 304 austenitic stainless steel samples were ground on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polished on a polishing machine with 2.5μm diamond paste until the sample surface was as smooth as a mirror without obvious scratches. After polishing, the surface was rinsed with ethanol and then blown dry with a polishing machine to prepare for erosion.

[0070] S2: Measure 6 ml of analytical pure hydrochloric acid and 8 ml of analytical pure anhydrous ethanol, pour them into 17 ml of deionized water, mix them, and then add 4.0 g of analytical pure ferric chloride solid and mix them evenly to obtain an etchant. Gently shake the volumetric flask containing the etchant to make the etchant solution uniform, and then pour the etchant into the beaker.

[0071] S3: Use tweezers to pick up the polished 304 austenitic stainless steel metallographic sample containing chromium carbide, immerse it into the etchant with the etched surface facing down for 4 seconds, observe the change in surface color, the surface of the sample is slightly dark gray, take out the sample and immediately rinse it with water, then quickly clean the etched surface of the sample with anhydrous ethanol, and then dry it with a hair dryer.

[0072] Comparative Example 1

[0073] S1: Pretreatment of 304 austenitic stainless steel. Grind the 304 austenitic stainless steel sample on 80#, 240#, 1200# and 3000# water sandpaper in turn, and then polish it on a polisher with 2.5μm diamond paste until the sample surface is as smooth as a mirror without obvious scratches. After polishing, rinse the surface with alcohol and then blow dry with a polisher to prepare for erosion.

[0074] S2: Use a cotton ball dipped in ferric chloride hydrochloric acid aqueous solution (5 g ferric chloride + 50 ml hydrochloric acid + 100 ml water) to gently rub the polished sample surface for 3 seconds. The sample surface appears dark gray. Rinse the sample surface with water to remove the etchant residue, then clean it with anhydrous ethanol and dry it with a hair dryer.

[0075] Experimental example:

[0076] The sample surface was observed with high resolution using a Zeiss ZEISS EVO18 scanning electron microscope (SEM), and the chemical composition of the precipitated phases of the examples and comparative examples was determined using an energy dispersive spectrometer (EDS).

[0077] The following are the observation results of the embodiment:

[0078] Figure 1 The observation result of the eroded surface of 304 austenitic stainless steel in Example 3 under the electron microscope 2000X field of view after erosion; Figure 2 The observation result of the eroded surface of 304 austenitic stainless steel in Example 3 under the electron microscope 10000X field of view after erosion;

[0079] Table 2 shows the composition content of the bright white particles and matrix obtained after etching in Example 3 after EDS scanning (the positions of the spectra in Table 2 are shown in Table 2). Figure 2 marked in the middle).

[0080] Table 2 Component contents of bright white particles and matrix positions after EDS scanning in Example 3

[0081]

[0082]

[0083] like Figure 1 As shown in the figure, under the 2000X field of view, many bright white spherical, water droplet-shaped or granular objects with clear boundaries can be seen, embedded in the grain boundaries or inside the grains. Figure 2 Bright white particles under the field of view (spectrum Figure 1 -5) and the matrix (spectrum 6-8) positions are scanned by EDS to confirm the composition and obtain the content of each component in Table 2. As shown in Table 2, the Cr content of the bright white particle component ranges from 32% to 45%, and the C content is above 9.5%, which is much higher than the content of the matrix component Cr and C element in Table 1. It can be judged that the white particles are chromium carbides. In summary, it is shown that the etchant of the present application can clearly display chromium carbides with clear boundaries after etching 304 austenitic stainless steel, and will not cause the chromium carbides to fall off during the etching process, or cause local black holes to appear on the eroded surface, which is conducive to the subsequent accurate analysis of the morphology and distribution of chromium carbides.

[0084] The following are the observation results of the comparison:

[0085] Figure 3 The results are the observation results of the eroded surface of 304 austenitic stainless steel in the comparative example under the electron microscope 5000X field of view after corrosion; Table 3 shows the composition content of the bright white particles obtained after corrosion in the comparative example and the matrix position after EDS scanning.

[0086] Table 3 Component contents of bright white particles and matrix positions in comparative example 1 after EDS scanning

[0087]

[0088]

[0089] like Figure 3 As shown in the figure, the 5000X field of view is full of holes and the complete chromium carbide morphology cannot be seen. The component contents of each spectrum after EDS scanning of the bright white particles and matrix positions obtained after etching are shown in Table 3 (the positions of each spectrum in Table 3 are in Figure 3), wherein the chromatogram component Cr content ranges from 17% to 21%, the C content is below 2%, and the Cr and C contents are both near the matrix component content in Table 1. This indicates that the etchant in the comparative example cannot clearly display chromium carbides with clear boundaries after etching 304 austenitic stainless steel, which will cause the chromium carbides to fall off during the etching process, or cause local black holes to appear on the eroded surface.

[0090] Compared with the prior art, the present invention has the following beneficial effects:

[0091] The present application is based on the formula of ferric chloride hydrochloric acid aqueous solution, which is a commonly used etchant for traditional austenitic stainless steel. By optimizing the ratio of hydrochloric acid to water and adding an appropriate amount of ethanol, an etchant specifically for observing chromium carbides in stainless steel is prepared. The chromium carbides after etching are bright white spheres, droplets or granules with clear boundaries, embedded in the grain boundaries or inside the grains.

[0092] First of all, the hydrochloric acid in the component not only effectively guarantees the erosion ability of the etchant, but also can ionize H + and Cl- ions, thereby inhibiting Fe 3+ The hydrolysis reaction maintains Fe 3+ The effective concentration of Fe 3+ Oxidation of the substrate.

[0093] Secondly, ethanol and water as solvents can dilute hydrochloric acid and reduce the overall concentration of the etchant, thereby slowing down the erosion depth in local areas. In addition, since the hydroxyl group (-OH) in the ethanol molecule is the polar part, and the ethyl group (-C2H5) is the non-polar part, the polarity of the ethanol molecule is lower than that of the water molecule (the dipole moment of ethanol is about 1.69D, while the dipole moment of the water molecule is 1.85D). The coordination between the two can control the erosion ability of the reagent within a moderate range, avoid the chromium carbide from falling off during the erosion process, or cause local black holes to appear on the eroded surface, thereby affecting the subsequent accurate observation and analysis of the morphology and distribution of chromium carbides; if only anhydrous ethanol is used as a solvent, it is difficult to achieve this effect.

[0094] Finally, ethanol and water solvents have good miscibility with ferric chloride, which can increase the reaction rate and ensure the uniformity of the etching process.

[0095] The mutual coordination between the above components enables the improved etchant to control the erosion ability and erosion rate within a moderate range and ensure the uniformity of the erosion process, thereby clearly displaying the chromium carbide boundaries. The chromium carbide particles after etching are not easy to fall off, which is conducive to the observation of its microstructure and improves the accuracy of the analysis of the content of related components.

[0096] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, the above technical features can be freely combined without departing from the concept of the present invention, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the coverage of the claims of the present invention.

Claims

1. An etchant for observing chromium carbides in stainless steel, characterized in that: The invention comprises the following components in parts by weight: 15-20 parts of deionized water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol and 3-5 parts of ferric chloride.

2. An etchant for observing chromium carbides in stainless steel according to claim 1, characterized in that: The hydrochloric acid is analytically pure hydrochloric acid, and the ethanol is anhydrous ethanol.

3. Use of the etchant according to any one of claims 1 to 2 in 304 austenitic stainless steel.

4. The use according to claim 3, characterized in that: The etching agent is used to etch 304 austenitic stainless steel, and chromium carbides in the 304 austenitic stainless steel can be observed after etching.

5. The use according to claim 4, characterized in that: Immerse the 304 austenitic stainless steel erosion surface in the etchant for etching. When the 304 austenitic stainless steel erosion surface turns dark gray, stop etching.

6. The use according to claim 4, characterized in that: After the etching is terminated, the 304 austenitic stainless steel is taken out and the eroded surface is first rinsed with deionized water and then with anhydrous ethanol.

7. The use according to claim 4, characterized in that: Before the 304 austenitic stainless steel is corroded, the method further includes: grinding and polishing the surface of the 304 austenitic stainless steel to be corroded.

8. The use according to claim 7, characterized in that: After the grinding and polishing, the surface to be etched of the 304 austenitic stainless steel is cleaned with ethanol.

9. A method for preparing an etchant for observing chromium carbides in stainless steel, characterized in that: include: The etching agent is prepared by uniformly mixing 15-20 parts by weight of water, 5.9-11.8 parts of hydrochloric acid, 3.9-7.9 parts of ethanol and 3-5 parts of ferric chloride.

10. The preparation method according to claim 9, characterized in that: The specific method for uniform mixing includes: pouring hydrochloric acid and ethanol into water in sequence and mixing, and adding ferric chloride and mixing evenly.